Memory for movement sequences in gymnastics: effects of age and skill level - Cadopi, M. (Journal of Motor Behavior, 1999)
The authors studied the performances of 8- to 13-year-old skilled (n = 30) and less skilled (n = 30) gymnasts on a gymnastics routine recall task by examining the role of memorization strategies and imagery ability. Subjects had to reproduce 3 movement sequences presented on videotape. The number of trials needed to achieve correct recall, the strategies employed, and the subjects' imagery ability were analyzed. Recall performance improved with age and skill level. Movement labeling was the most prevalent strategy used; its frequency increased with age, although it did not lead to better recall performance. Performance was higher, however, among subjects with better imagery skills. The role of strategy development in the age-related improvement in memory performance was not clearly demonstrated. The effect of skill level is interpreted in terms of knowledge bases and kinesthetic movement encoding.